Електросапа – культиватор «Мрія» - Руденко, Т. В.; Амосов, В. В.; Кулєшков, Ю. В.; Руденко, І. Т.; Rudenko, T.; Amosov, V.; Kulyeshkov, Yu.; Rudenko, I. (ЦНТУ, 2024)
В даній статті запропоновано конструкцію універсальної електросапи – культиватора з балансувальним ведучим колесом для проведення міжрядної обробки просапних культур. Особливістю даної конструкції є те, що дана машина обладнана електричним двигуном постійного струму з вбудованим редуктором, живлення якого здійснюється за рахунок акумуляторної батареї. Також пропонується дообладнати її пристроєм, для виконання внутрішньорядного просапування. In this article, we propose the design of a universal electric hoe - a cultivator with a balancing drive wheel for inter-row cultivation of row crops. Currently, chemical methods and mechanical loosening are widespread in modern agriculture, but concerns about the use of herbicides, especially in "organic farming," leave no choice. We propose a machine that allows for inter-row cultivation of any row crops, even by a child. The proposed device is to be equipped with an electric motor with an electric battery, which will allow for greater mobility, low noise and vibration levels, as well as a set of tools to perform all technological operations when growing row crops.
Electric hoe - cultivator "Mriya"
Keywords: ручний електрокультиватор; міжрядна та внутрішньорядна обробка; електросапа; ведуче колесо; hand-held electric cultivator; inter-row and intra-row cultivation; electric hoe; drive wheel